A Retrospective Study on the Effectiveness of Ixekizumab After Treatment With Secukinumab for Patients With Active Psoriatic Arthritis. Issue 1 (January 2022) - Darabian, Saman; Badii, Maziar; Dutz, Jan P.; Chan, Jonathan
Objectives: This study aims to evaluate clinical responses in patients with active psoriatic arthritis who, despite secukinumab 300 mg subcutaneous monthly, are switched to ixekizumab 80 mg subcutaneous every four weeks.Methods: We conducted a chart review of adult patients with psoriatic arthritis treated at one clinical center. We identified all patients with active inflammatory arthritis who were switched from secukinumab to ixekizumab. Baseline demographics such as disease duration, age, gender, number of previous DMARDs, and previous time on secukinumab were collected. We collected clinical outcome data such as tender and swollen joint count, enthesitis based on SPARCC score, dactylitis, psoriasis severity, CRP, and BASDAI if axial involvement was present.Results: Eight of 10 patients were included in the analysis. Most patients were female, average age 62 years old, and had been on secukinumab for an average of 79 weeks. Twelve weeks following switch to ixekizumab, 6/8 had improvement in tender joint count, 6/8 improved in swollen joint count, 2/2 had resolution of enthesitis, 4/4 had resolution of dactylitis, 5/6 had improvement in psoriasis severity, 1 patient had absolute improvement of 2.3 in BASDAI, and 7/8 had improvement in the CRP level.Conclusions: Patients with active psoriatic arthritis despite treatment with secukinumab may still have a clinical response following treatment with another anti-IL17 agent. Larger studies will be required to confirm this finding, and studies which emphasize dactylitis and enthesitis outcomes will be needed as most patients did not have activity in these domains.